La Tabula De ciuitate Dei dite de Robert Kilwardby. Problèmes d’attribution et tradition manuscrite - Brix, Antoine (Revue d'études augustiniennes et patristiques, 2014)
From the 18th century onwards, the Dominican friar Robert Kilwardby (d. 1279) has been considered the author of the anonymous alphabetical table on Augustine’s De ciuitate Dei copied in manuscripts Paris, BnF, lat. 2073, 2074, 2075, among other codices. This paper intends both to disprove such an assumption, for which there is no scientific evidence whatsoever, and to establish the manuscript tradition of the work in question, which happens to be spread in the whole of Europe. Furthermore, two other hypothetical authors are discussed: some of the manuscripts bear the name of Aymeric of Piacenza (d. 1327), master of the Dominican order, as that of the author; and Léopold Delisle once considered, although he was not followed by any scholar in this opinion of his, that the table was to be ascribed to Jean Bernier de Fayt, a very prolific Benedictine compiler (d. 1395).